Abundant naphthenic acids in oil sands process-affected water: Studies by synthesis, derivatisation and two-dimensional gas chromatography/high-resolution mass spectrometry - West, C.; Scarlett, Alan; Pureveen, J.; Tegelaar, E.; Rowland, S. (2013)
RATIONALE The large volumes of 'supercomplex' mixtures of reputedly toxic organic compounds in acidic extracts of oil sands process-affected waters (OSPW) represent a challenging goal for complete characterisation. To date, comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry (GCxGC/TOFMS) has allowed the acquisition and interpretation of numerous electron ionisation mass spectra including many of those confirmed to be tricyclic and pentacyclic carboxylic acids by reference to the spectra and retention positions of authentic or synthetic compounds. This has allowed the toxicities of some of the identified acids to be determined and their environmental significance to be better assessed. METHODS Synthesis, derivatisation (methyl, trideuteriomethyl and trimethylsilyl esters) and GCxGC/TOFMS with nominal mass and higher mass accuracy (ca. 5 ppm) were used to study three abundant unknown acids present in OSPW samples from two different industrial suppliers. RESULTS GCxGC/TOFMS with nominal mass accuracy, of methyl, trideuteriomethyl and trimethylsilyl esters of three abundant acids in two OSPW samples, produced mass spectra consistent with their assignment as either C16 tetracyclic acids or as isobaric pentacyclic C15 hydroxy acids ('O3') or sulfur-containing ('SO2') species. The synthesis of several isomeric pentacyclic C15 hydroxy acids and examination of the GCxGC retention times and mass spectra (nominal mass) of their derivatives suggested that the unknown OSPW acids were not hydroxy acids, and GCxGC/TOFMS with higher mass accuracy ruled out the possibility. The possibility that they were isobaric 'SO2' species could also be dismissed as this was inconsistent with accurate masses, the derivatisation reactions observed, the fragmentation patterns and the isotope distributions, which excluded the presence of sulphur. CONCLUSIONS The data support the contention that the three abundant unknowns were indeed C16 tetracyclic acids. An equally rigorous approach will be necessary to characterise further acids in such mixtures. This is important so that chemistry can be used to guide the search for toxic modes of action. Copyright © 2012 John Wiley & Sons, Ltd.